2018
DOI: 10.1111/are.13816
|View full text |Cite
|
Sign up to set email alerts
|

The effect of background colour and lighting of the aquarium on the body pigmentation of the peppered shrimp Lysmata wurdemanni

Abstract: During a 100-day period, the effect of two background colours (white and black) of fish tanks and two light spectrum (red and white) on the growth and pigment expression of juvenile peppermint shrimp Lysmata wurdemanni was evaluated. A completely randomized experimental design was implemented with four treatment groups and a control group (natural illumination). At the end of the study, the survival, weight gain and total carotenoid content in the abdomen and cephalothorax (spectrophotometry) were evaluated, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The lower RGB value obtained for fish reared under darkness environment indicates higher pigmentation compared to fish under light condition. Our observation is in line with the results obtained for peppered shrimp, Lysmata wurdemani, which indicated high pigmentation under darkness background (Díaz, Martha, Hernández, Iván, & Rostro, 2018). Fish under darkness had high pigmentation of reddish-pink colour, which is highly preferred by consumers (Haque et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The lower RGB value obtained for fish reared under darkness environment indicates higher pigmentation compared to fish under light condition. Our observation is in line with the results obtained for peppered shrimp, Lysmata wurdemani, which indicated high pigmentation under darkness background (Díaz, Martha, Hernández, Iván, & Rostro, 2018). Fish under darkness had high pigmentation of reddish-pink colour, which is highly preferred by consumers (Haque et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings may be important for shrimp breeders. Using the optimum substratum colour may lead to their faster growth and lower aggression [ 16 , 22 ], and, as a consequence, to higher breeding success and more intense colouration [ 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…After photography, the copepod individuals were immediately transferred to a 12-well culture plate (3.5 mL/ well), where it was temperately cultivated for further selection. Simultaneously, the RGB value corresponding to the prosome and urosome areas, where the pigments primarily accumulated, was analyzed using Adobe Photoshop CS6 software (Adobe Systems, CA, USA) following the protocol described by Díaz‐Jiménez et al 25 . This approach enabled a rapid assessment of the RGB values for living copepod individuals with no mortality caused, serving as an indicator of the astaxanthin-associated trait for selective breeding in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Astaxanthin, the most dominant form of carotenoid pigments in copepods 14 , 22 , is correlated with their body color 23 , 24 . RGB value has been utilized as an indicator for carotenoid content in aquatic animals 25 , 26 . Although the function and causation of astaxanthin accumulation in copepods are not fully understood, studies suggested its role in protecting against oxidative stresses induced by ultraviolet radiation 27 and metal toxicants 28 .…”
Section: Introductionmentioning
confidence: 99%